Enticed by you - Wright, Elle (Wright, Elle. Wellspring series., 2018)
With his father ailing and incapacitated, Parker Wells, Jr. has a bold new vision for the company he now heads. For starters, he wants to heal the rifts his father<U+2019>s ruthless tactics have created in the community<U+2014>and within his own family. But when Parker is rear-ended by a gorgeous stranger, he finds himself torn between business and pleasure . . . Crashing her car is not how corporate attorney Kennedi Robinson wanted to announce her return to town, especially since the man she hit is the same one who<U+2019>s trying to rip her aunt<U+2019>s livelihood and land out from under her. Kennedi knows better than to fall for Parker<U+2019>s charms<U+2014>and she<U+2019>s primed for battle.